EXPORT PROMOTION POLICY AND SUSTAINABLE ECONOMIC GROWTH: THE CASE OF KAZAKSTAN - Rayev, Olzhas Kairbekuly (Graduate School of International Studies Ajou University, 2006)
Kazakstan, occupying strategically important position, being located right in the center of Eurasia, possessing incredibly rich natural resources, huge territory and well educated population, in conditions of right economy, finance and trade policy provided, has good chances to became one of the advanced and significant economies of Eurasia in the future. The booming growth of Kazakstan`s economy and it’s even greater potential raises hopes for bright future of the country. But at the same time Kazakstan should not underestimate its vulnerability and danger of so called resource course. Many countries all around the world, which are rich in natural resources usually, have quite poor growth performance, over dependency on their mono-products and on abruptly swinging demand for their raw materials in international markets. It is clear that the natural resources abundance does not necessarily leads to economic development and prosperity of any country in long perspective. Kazakstan has successfully overcome difficulties of transition period and currently has aspiration and actual potential to build a post-industrial, high-tech economy with capabilities in aerospace, biotechnology, software technologies, peaceful uses of atomic energy and other industrial sectors. Meanwhile it is believed that current impetuous growth of Kazakstan`s economy, that country enjoys for last six years is based mostly on oil export revenues and should not be considered as sustainable in the long run. Analyzing the current economic standings of Kazakstan, threats and trends, structure of the economy and the efforts taken for its diversification, which is urgently and vitally needed for obtaining more adequate and worthy position in the international economic arrangement, and taking into consideration accelerated and more intense competition among countries and transnational corporations, new high-technologies development and the processes of globalization, Kazakstan should examine sustainability of its economic growth, economy diversification and current export promotion policy. The aims and objectives of this study is to find out if current export promotion policy of Kazakstan is sufficient and if it contributes effectively to the steady economic growth, to determine main directions of formation, improvement and development of export promotion policy needed to maintain sustainable economic growth of Kazakstan in the long run.
학위논문(석사)--아주대학교 국제대학원--국제경영학과,2006. 8